The first enantioselective total synthesis of lantalucratin C and determination of its absolute configuration. Issue 38 (23rd September 2015) - Ogata, Tokutaro; Tanaka, Manami; Ishigaki, Momoe; Shimizu, Maki; Nishiuchi, Arisa; Inamoto, Kiyofumi; Kimachi, Tetsutaro
Abstract: Described here is the first enantioselective total synthesis of lantalucratin C, which was isolated from the rainforest plant Lantana involucrata, and which possesses anti-tumor activity. The OH group on the aromatic ring was systematically introduced by an appropriate management of the OH protecting groups. The alkyl side chain connected to a chiral carbon center was incorporated by directed ortho -lithiation of naphthalenes followed by asymmetric epoxidation. The furano-1, 2-naphthoquinone skeleton was constructed from 3-hydroxyalkylnaphthalene by CAN-mediated oxidative cyclization. The absolute stereochemistry at the C2 carbon was assigned the R -configuration by the Kusumi–Mosher method. Graphical abstract: